The development of physical performance during elite soccer matches - can motion analysis contribute to identify fatigued footballers? - Kjøsnes, T. N. (2014)
Background: The physical performance of soccer players at the end of matches, measured by motion analysis variables, could potentially contribute to identify how fatigued they are. Such information would be valuable for the coaching staff in order to optimize the players` training load and avoid injuries in the following days. Further knowledge regarding the development of physical performance during competitive games is, however, needed.